Oral corticosteroids stewardship for asthma in adults and adolescents: A position paper from the Thoracic Society of Australia and New Zealand. Issue 12 (29th September 2021) - Blakey, John; Chung, Li Ping; McDonald, Vanessa M.; Ruane, Laurence; Gornall, John; Barton, Chris; Bosnic‐Anticevich, Sinthia; Harrington, John; Hew, Mark; Holland, Anne E.; Hopkins, Trudy; Jayaram, Lata; et al.
Abstract: Oral corticosteroids (OCS) are frequently used for asthma treatment. This medication is highly effective for both acute and chronic diseases, but evidence indicates that indiscriminate OCS use is common, posing a risk of serious side effects and irreversible harm. There is now an urgent need to introduce OCS stewardship approaches, akin to successful initiatives that optimized appropriate antibiotic usage. The aim of this TSANZ (Thoracic Society of Australia and New Zealand) position paper is to review current knowledge pertaining to OCS use in asthma and then delineate principles of OCS stewardship. Recent evidence indicates overuse and over‐reliance on OCS for asthma and that doses >1000 mg prednisolone‐equivalent cumulatively are likely to have serious side effects and adverse outcomes. Patient perspectives emphasize the detrimental impacts of OCS‐related side effects such as weight gain, insomnia, mood disturbances and skin changes. Improvements in asthma control and prevention of exacerbations can be achieved by improved inhaler technique, adherence to therapy, asthma education, smoking cessation, multidisciplinary review, optimized medications and other strategies. Recently, add‐on therapies including novel biological agents and macrolide antibiotics have demonstrated reductions in OCS requirements. Harm reduction may also be achieved through identification and mitigation of predictable adverse effects. OCS stewardship should entail greater awareness of appropriate indications for OCS prescription, risk–benefits of OCS medications, side effects, effective add‐on therapies and multidisciplinary review. If implemented, OCS stewardship can ensure that clinicians and patients with asthma are aware that OCS should not be used lightly, while providing reassurance that asthma can be controlled in most people without frequent use of OCS. Abstract : See related Editorial